Languages of Discrimination and Racism in Twentieth-Century Italy
XII, 297 p. 4 illus.
Keywords: This volume represents one of the first extensive studies that investigates the persistence of questions of race and racism in Italy from the liberal age to the present, through colonialism, Fascism and post-war Italy. It adopts an interdisciplinary perspective to investigate the intertwining of the cultural, social, legislative and political dynamics of discrimination in Italy’s past and present. Drawing upon the expertise of historians, political scientists, sociologists, scholars of literature and experts in cultural studies, the original essays collected in this volume show a remarkable continuity and the persistence of racism in the Italian cultural and political discourse, in society and in the representation of Others. They also speak of the shifting of practices of Othering from one group to another in different historical contexts. Marcella Simoni is Associate Professor of History and Institutions of Asia at Ca’ Foscari University of Venice, Italy and isalso affiliated with New York University, Florence. Her research interests include Jews in Asia, civil society in the Israeli-Palestinian conflict, the history of medicine and public health, a focus on history, memory and trauma, cinema in the Middle East. Davide Lombardo is Lecturer in History and Liberal Studies at New York University, Florence, Italy and also teaches Political Science at Kent State University Florence. His research focuses on European culture from the nineteenth to the twentieth centuries.